Primary hyperaldosteronism sensitive to glucocorticoid treatment - Cruz jesus, Lourdes; Veiga e Moura, António; B. Veiga, Maria Rosário; Ferreira, Ma´rio Rui; Miraldo, Manuel (Portuguese Journal Internal Medicine, 1997)
The autors describe the clinical case of a female patient with arterial hypertension, secondary to primary hyperaldosteronism, which proved to be sensitive to treatment with glucocorticoid steroids. Emphasis is placed on the sequence of complementary tests which lead to the final diagnosis, as well the contribuition that ambulatory blood pressure monitoring had, in the process of diagnostic evaluation and efficient therapeuthic control.